Developing the relationship between organizational capability and sustainable development dimensions with the mediating role of organizational focus in the sustainable electricity supply chain - Seyed Nader Mirian; Abbas Sheikh Aboumasoudi; Ali Sheikh Aboumasoudi; Shakiba Khademolqorani (Sustainable Futures)
This study examines organizational capabilities as a critical success factor in the electricity industry and analyzes their role in achieving sustainable development. Sustainable development, as a multidimensional concept, requires simultaneous attention to economic, social, and environmental aspects. In this regard, empowering organizations through enhancing effective leadership, strategic thinking, appropriate structure, and strong organizational culture is essential to increase resilience and responsiveness to complex challenges. The research findings indicate that transparency, the adoption of modern technologies, and the enhancement of knowledge and human capital significantly contribute to improving organizational performance and reducing operational risks.Moreover, regional and international collaborations in energy exchange and investment in electricity import and export infrastructures create new opportunities for strengthening the competitive position of organizations. On the other hand, formulating incentive policies and managerial mechanisms to reduce energy losses and increase efficiency can guide employees toward achieving organizational goals, resulting in cost reduction and increased profitability.This study presents a comprehensive framework for developing organizational capacities that can serve as a guideline for managers in navigating the dynamic environment of the electricity industry. Ultimately, the research emphasizes that only through the effective integration of technology, risk management, and human capital development can sustainable development and long-term competitiveness be achieved.